A novel Biochar modified by Chitosan-Fe/S for tetracycline adsorption and studies on site energy distribution. (December 2019) - Liu, Juanli; Zhou, Baiqin; Zhang, Hong; Ma, Juan; Mu, Bin; Zhang, Wenbo
Graphical abstract: Highlights: A novel waste municipal sludge based Biochar modified with Chitosan-Fe/S was prepared for removal of tetracycline in water. Comparison in adsorption behaviors between Biochar and composite was investigated. Concrete adsorption mechanisms of the composite for removal of tetracycline were discussed in detail. Site energy distribution of surface properties for Biochar and composite was studied. Abstract: A novel wasted sludge-based Biochar modified by Chitosan and Fe/S (BCFe/S) was prepared for tetracycline (TC) removal from water. To investigate the similarities and differences in adsorption behaviors between Biochar and BCFe/S, characterization, kinetics, isotherms and thermodynamics were discussed. The studies on site energy distribution (SED) were also presented. The results showed that the maximum TC adsorption amount was 51.78 mg/g for Biochar, while it was 183.01 mg/g for BCFe/S-4. Meanwhile, electrostatic attraction, π-π stacking, pore filling, silicate bonding and hydrogen bonding were the main adsorption mechanisms for TC removal by Biochar. Besides above mechanisms, chelating and ion exchange were also accounted for adsorption mechanisms for TC uptake by BCFe/S-4. Moreover, SED results revealed that the surface of Biochar was more homogeneous while the surface of BCFe/S-4 was more heterogeneous at higher temperature. Findings of this work could offer valuable information in designing adsorbents and investigating adsorption mechanisms.